2017
DOI: 10.1177/0886260517725735
|View full text |Cite
|
Sign up to set email alerts
|

Peer Influence on IPV by Young Adult Males: Investigating the Case for a Social Norms Approach

Abstract: Nearly 32% of women report experiencing physical violence from an intimate partner and more than 8% report being raped by a significant other in their lifetime. Young people's perceptions that their peers perpetrate relationship violence have been shown to increase the odds of self-reported perpetration. Yet, limited research has been conducted on this relationship as individuals begin to age out of adolescence. The present study sought to examine the link between the perception of peer perpetration of intimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“… 50 52 For young men, it is possible that a relative lack of relationship experiences, masculine-identity seeking and vulnerability to peer influence 50 52 increase their tendency to perpetrate violence. 53 These findings have implications for the design of future preventive interventions for different subpopulations, especially men in the younger age groups.…”
Section: Discussionmentioning
confidence: 99%
“… 50 52 For young men, it is possible that a relative lack of relationship experiences, masculine-identity seeking and vulnerability to peer influence 50 52 increase their tendency to perpetrate violence. 53 These findings have implications for the design of future preventive interventions for different subpopulations, especially men in the younger age groups.…”
Section: Discussionmentioning
confidence: 99%
“…, McKool et al . ), are highly gendered. As a result, the emerging stream of work on ‘social norms’ has begun to elide with earlier efforts to address ‘gender norms’, creating some confusion.…”
Section: Introductionmentioning
confidence: 99%
“…(Finer & Philbin, 2013;Glick & Golden, 2014;Holmes, 2009;Sandfort et al, 2008)There is also no published research on how coercion may factor into age-appropriate sexual relationships of adolescent MSM, but one study of young adult males showed a high prevalence (67%) of sexual violence with partners. (McKool, Stephenson, Winskell, Teten Tharp, & Parrott, 2017) A new adolescent couples HIV prevention trial is designed to capture some of this relationship data and may help inform better measurement of early sexual partnership dynamics. (Gamarel, Darbes, Hightow-Weidman, Sullivan, & Stephenson, 2019) Finally, the study was intended to identify age of initiation of sex with men, but we did not ask questions about the age of initiation of sex with females to allow us to determine an absolute age of first sex for comparability with other previous general population studies.…”
Section: Discussionmentioning
confidence: 99%